Prime boost vaccination with viral vectors targeting apical membrane antigen1 - Biswas, S (2013)
Apical membrane antigen 1 (AMA1) is a leading candidate vaccine antigen against blood stage malaria and several clinical trials using mostly protein-in-adjuvant vaccines have shown limited success. This thesis describes the development of recombinant adenoviral (AdHu5) and poxviral (MVA) vectors encoding AMA1 from Plasmodium chabaudi murine parasites. In this murine malaria model, AdHu5 and MVA encoding AMA1 when used in a heterologous prime boost regime showed excellent immunogenicity, both humoral and cellular. The vaccination regime was protective against blood stage challenge and both antibodies and CD4+ T cells found to be important for vaccine induced blood stage protection. In parallel to this novel P. falciparum vaccines encoding AMA1 were also developed and administered in a similar prime boost regime to mice and rabbits. The vaccination regime induced cellular immune response and high titre antibodies against AMA1 and these antibodies showed growth inhibitory activity against the homologous parasite strain. In an effort to overcome the issue of antigenic polymorphism and to circumvent pre-existing immunity to human adenovirus, biallelic simian and human adenoviral vectors and MVA encoding AMA1 vaccines were also developed and administered to mice and macaques. These vectors also induced high titre antibodies and the serum from macaques was found to have growth inhibitory activity. These vaccine candidates are now being taken forward to Phase I/II clinical trials in Oxford. This work also described the attempt to improve MVA as a antibody inducing vector to allow better antibody mediated immunity to blood stage malaria.